High thermoelectric performance in supersaturated solid solutions and nanostructured n-type PbTe–GeTe - Luo, Zhong-Zhen (2020)
Sb-doped and GeTe-alloyed n-type thermoelectric materials that show an excellent figure of merit ZT in the intermediate temperature range (400–800 K) are reported. The synergistic effect of favorable changes to the band structure resulting in high Seebeck coefficient and enhanced phonon scattering by point defects and nanoscale precipitates resulting in reduction of thermal conductivity are demonstrated. The samples can be tuned as single-phase solid solution (SS) or two-phase system with nanoscale precipitates (Nano) based on the annealing processes. The GeTe alloying results in band structure modification by widening the bandgap and increasing the density-of-states effective mass of PbTe, resulting in significantly enhanced Seebeck coefficients. The nanoscale precipitates can improve the power factor in the low temperature range and further reduce the lattice thermal conductivity (κlat). Specifically, the Seebeck coefficient of Pb0.988Sb0.012Te–13%GeTe–Nano approaches −280 µV K−1 at 673 K with a low κlat of 0.56 W m−1 K−1 at 573 K. Consequently, a peak ZT value of 1.38 is achieved at 623 K. Moreover, a high average ZTavg value of ≈1.04 is obtained in the temperature range from 300 to 773 K for n-type Pb0.988Sb0.012Te–13%GeTe–Nano.